Country image and satire in sport management: analyzing America through sports in South Park. Issue 1 (2nd January 2023) - Dubinsky, Yoav
Abstract: Since the 1990s, the animated political satire South Park ( SP ) has received ample media and scholarship critiques for the way it portrays the United States. The research question this study addresses is: how are the US and Americans reflected through sports in SP ? The study is based on narrative inquiry and content analysis of 307 episodes in 23 seasons between 1997 and 2019. After three coding rounds of 114 identified sports-related episodes, six themes emerged from the data: (a) capitalism and morality, (b) race and historic injustice, (c) gender and sex, (d) sports and education, (e) lifestyle, and (f) 'them'. The findings suggest that social struggles and freedom of speech are central in an American society and in the image of the USA. The study expands literature on country image emphasizing the significance of using critical theories to better understand the intersections between sports, culture, and 'Brand America' and how they manifest in real-life challenges sports management practitioners need to resolve.